2022
DOI: 10.1177/02646196221104902
|View full text |Cite
|
Sign up to set email alerts
|

Intersectionality and access to visual rehabilitation services: Experiences of people with low vision, a qualitative study

Abstract: Low vision is a condition of visual impairment, generated by an underlying pathology that affects visual functioning and the development of daily activities. In the field of visual impairment, the developments in the analysis of access to rehabilitation services are scarce and incipient. The study approaches the understanding of the experiences of people with low vision in Medellín, Colombia, in their search for visual rehabilitation services. Ethnographic collective case study was conducted. Intersectionality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
4
0
3
Order By: Relevance
“…Las ayudas electrónicas no se encuentran disponibles fácilmente en el mercado en Colombia; la mayoría deben ser importadas y no están cubiertas por el sistema de salud 51 . Los costos varían entre una lupa electrónica de US$ 190, un circuito cerrado de televisión de US$ 280 y un dispositivo montado en la cabeza de US$ 2796.…”
Section: Consideraciones Para La Implementaciónunclassified
See 2 more Smart Citations
“…Las ayudas electrónicas no se encuentran disponibles fácilmente en el mercado en Colombia; la mayoría deben ser importadas y no están cubiertas por el sistema de salud 51 . Los costos varían entre una lupa electrónica de US$ 190, un circuito cerrado de televisión de US$ 280 y un dispositivo montado en la cabeza de US$ 2796.…”
Section: Consideraciones Para La Implementaciónunclassified
“…Los costos varían entre una lupa electrónica de US$ 190, un circuito cerrado de televisión de US$ 280 y un dispositivo montado en la cabeza de US$ 2796. Existen estudios de otros países en los que se demuestran que son costo-efectivos 51 . Los pacientes podrían aceptar la intervención con ayudas ópticas electrónicas si ellos pudieran evaluar su efectividad y la aceptaran de acuerdo con el tamaño, la portabilidad y la accesibilidad.…”
Section: Consideraciones Para La Implementaciónunclassified
See 1 more Smart Citation
“…Electronic aids are not readily available in the market in Colombia. Most of them need to be imported and are not covered by the health-care system 51 . Price goes from USD 190 for electronic magnifiers, USD 280 for closed-circuit TVs, and USD 2796 for head-mounted devices.…”
Section: Implementation Considerationsmentioning
confidence: 99%
“…However, Khimani, Redmon [ 32 ] and Sarika, Venugopal [ 33 ] recently showed that investigating both point of views can be beneficial as it generates a broad perspective, which contributes to a better understanding about factors influencing the referral pathways to LVS. Furthermore, earlier studies were mainly conducted in countries with no systematic national provision or financial coverage of LVS and/or with a low income, such as the United States [ 25 , 28 , 32 ], Australia [ 30 , 31 ], Canada [ 23 ], India [ 29 , 33 ], Colombia [ 34 ] and Ghana [ 35 ]. As a consequence, insights to referral barriers and facilitators are particularly lacking from high-income countries in general with different types of healthcare and coverage systems.…”
Section: Introductionmentioning
confidence: 99%